Cation-induced coagulation of aquatic plant-derived dissolved organic matter: Investigation by EEM-PARAFAC and FT-IR spectroscopy. (March 2018) - Liu, Shasha; Zhu, Yuanrong; Liu, Leizhen; He, Zhongqi; Giesy, John P.; Bai, Yingchen; Sun, Fuhong; Wu, Fengchang
Abstract: Complexation and coagulation of plant-derived dissolved organic matter (DOM) by metal cations are important biogeochemical processes of organic matter in aquatic systems. Thus, coagulation and fractionation of DOM derived from aquatic plants by Ca(II), Al(III), and Fe(III) ions were investigated. Metal ion-induced removal of DOM was determined by analyzing dissolved organic carbon in supernatants after addition of these metal cations individually. After additions of metal ions, both dissolved and coagulated organic fractions were characterized by use of fluorescence excitation emission matrix-parallel factor (EEM-PARAFAC) analysis and Fourier transform infrared (FT-IR) spectroscopy. Addition of Ca(II), Fe(III) or Al(III) resulted in net removal of aquatic plant-derived DOM. Efficiencies of removal of DOM by Fe(III) or Al(III) were greater than that by Ca(II). However, capacities to remove plant-derived DOM by the three metals were less than which had been previously reported for humic materials. Molecular and structural features of plant-derived DOM fractions in associations with metal cations were characterized by changes in fluorescent components and infrared absorption peaks. Both aromatic and carboxylic-like organic matters could be removed by Ca(II), Al(III) or Fe(III) ions. Whereas organic matters containing amides were preferentially removed by Ca(II), and phenolic materials were selectively removed by Fe(III) or Al(III). These observations indicated that plant-derived DOM might have a long-lasting effect on water quality and organisms due to its poor coagulation with metal cations in aquatic ecosystems. Plant-derived DOM is of different character than natural organic matter and it is not advisable to attempt removal through addition of metal salts during treatment of sewage. Graphical abstract: Highlights: Cation-induced coagulation of plant-derived DOM was investigated by EEM and FT-IR. Removal efficiencies of DOM by Fe(III), Al(III) were greater than that by Ca(II). Plant-derived DOM was more difficult to remove than humic OM by metal cations. Aromatic and carboxylic-like OM could be removed by Ca(II), Al(III) or Fe(III). Amides were selectively removed by Ca(II), phenols were removed by Fe(III), Al(III). Abstract : The selective binding and coagulation of plant-derived DOM by Ca(II), Al(III), and Fe(III) were demonstrated.